(untitled) - Douglas C Dacy (Cambridge, 1986)
The book traces the economic history of South Vietnam from 1955 to 1975. A generous foreign aid program was designed to pay local troops and improve the standard of living of the population. The book documents this growth in national income and the progress or lack thereof in a number of development indicators. It discusses the goals of United States economic aid and measures the net resources transferred. Additionally, the book analyzes wartime inflation and the Vietnamese tax system. Finally, economic development in South Vietnam is compared to that in Israel, South Korea, and Taiwan, there nations that faced high military threats during the same period
Keywords: economic assistance - american - vietnam,vietnam - economic conditions,vietnam - politics and government - 1945-1975